String corrections to gauge couplings from a field theory approach - Ghilencea, D; Nibbelink, S (2003)
An effective field theory approach is introduced to compute one-loop radiative corrections to the gauge couplings due to Kaluza-Klein states associated with a two-torus compactification. The results are compared with those of the string in the field theory 'limit' alpha' --> 0. The whole U and the leading T moduli dependence of the gauge-dependent part of the string corrections to the gauge couplings can be recovered using the effective field theory approach.